HER2 testing in gastric cancer: results of a German expert meeting - Lordick, Florian; Gaiser, Timo; Hofheinz, Ralf-Dieter (Journal of cancer research and clinical oncology, 2017)
Valid HER2 testing is essential for optimal therapy of patients with HER2-positive gastric cancer and the correct use of first-line chemotherapy. While testing for HER2 status in breast cancer is routinely performed, this is not the case for HER2 testing in gastric cancer and it is usually only performed on clinician request. An interdisciplinary German expert group (pathologists and clinicians) took the challenges of HER2 testing in gastric cancer as an opportunity to address essential aspects and questions for the practical use of HER2 testing in this indication. The recommendations made in this manuscript reflect the consensus of all participants and reflect their opinions and long-term experience in this field.